An Interview with Leonard Kleinrock. - Varghese, George (Communications of the ACM, 2019)
An interview with computer scientist Leonard Kleinrock is presented. He discusses his educational progress in electrical engineering including his work at Lincoln Labs, his research into packet communication and queueing theory and its use in ARPANET, and looks at the future in networking and distributed systems.